A microwave-assisted synthesis of 3,4-dihydropyrimidin-2(1H)-one/thione derivatives using nanocrystalline MgFe2O4 as catalyst - Ladole, Chandrashekhar Arunrao; Salunkhe, Nilesh Govindrao; Bhaskar, Ravindra Sakharam; Aswar, Anand Shankarrao (European Journal of Chemistry, 2014)
3,4-Dihydropyrimidin-2(1H)-one/thione derivatives were synthesized in moderate to high yields via one-pot three component Biginelli reaction of aldehydes, ethyl acetoacetate and urea/thiourea in the presence of nanocrystalline MgFe2O4 as an efficient catalyst, in microwave irradiation under solvent free condition. This protocol offers several advantages including good yields of products, short reaction time and easy work-up procedure.